Exploring the interactions between protein coronated CdSe quantum dots and nanoplastics. (24th March 2021) - Chakraborty, Debolina; Naik, Sanjay; Kumar, Sanjit; Chandrasekaran, N.; Mukherjee, Amitava
Abstract : QDs after protein coronation can undergo sequential interaction with other pollutants which may alter the physiochemical property of the QDs and influence the stability of the corona proteins. Abstract : It is now established that metastable colloidal nanoparticles (NPs) are subjected to interactions with proteins in biological media leading to the formation of a protein corona on the NPs. The physiochemical and biological activity of the NPs is further determined by the bio–nano interface. However, in a realistic biosystem, multiple layers of interaction that the NPs may encounter even after protein coronation are generally overlooked. In the present study, carboxy and amine-functionalized CdSe quantum dots (QDs) were utilized as the primary NPs for protein corona formation using fetal calf serum. The quantitative and the qualitative aspects of the protein corona varying with respect to the surface functionalization of the QDs were analyzed. A second layer of complexity was added in the experimental setup by interacting the coronated-QDs with nanoplastics as a major pollutant source. The colloidal stability and the physiochemical parameters of the coronated-QDs in the presence of three differently functionalized polystyrene beads (plain, aminated, and carboxylated) were assessed using transmission electron microscopy, dynamic light scattering, and zeta-potential measurements. A complex interplay of interactive forces and direct bonding of amino acids with the benzene ring of the PS-beads led to the development of a coronated-QD–PS complex in the size range of 400 nm. To assess the overall protein leaching, the coronated-QD–PS complex was further subjected to different pH-triggers. Atomic absorption spectroscopy was used to analyze the combinatorial effect of the protein corona and the PS-beads on the Cd 2+ ion release from the QDs. The novel approach of the study aims to include the complexities of a realistic reaction milieu wherein NP interactions are not just limited to proteins.